KESALAHAN BERBAHASA PADA KARANGAN DESKRIPSI SISWA KELAS VII UPT SMP NEGERI 2 BARANTI - Nurwahida, Nurwahida; Aswadi, Aswadi; Hanafi, Muhammad; Kamal, Kamal (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
The purpose of this study is to describe the form of spelling errors contained in students' essays. Students‘ description essay of Class VII UPT SMP Negeri 2 Baranti is the source of data, and spelling errors in students’ description essay are the research data. The techniques used to collect data include reading and note-taking techniques. The researcher and data cards as instruments. Data analysis used categorization, tabulation, and conclusion techniques. The results showed that there were errors in the use of Indonesian spelling in the description essays of seventh grade students of SMP Negeri 2 Baranti; there were errors in the use of capital letters, word writing errors, and punctuation errors. Students make Indonesian spelling mistakes because they are less careful and do not pay attention to correct spelling.